Práticas corporais nas comunidades quilombolas : significados das manifestações culturais na Escola de Monte Alegre - Carvalho, Heloisa Ivone da Silva de (2014)
This study presents the main aim of discussing bodily practices in the context of a Quilombo community, considering the existence of a relationship between this community and the discipline of Physical Education in the appropriation of culture. Research that subsidizes this text occurred from 2006 to 2012 through the lifting of the state of art in major magazines of Physical Education and database CAPES and associated teacher interviews, managers and students of the School of Basic Education of Monte Alegre in 2012 and 2013, with observations related to bodily practices, and document analysis. This research is qualitative in nature, where we dialogue with Minayo (1996), and we propose to work with the meanings of bodily practices because they respond to the particularities of the maroon culture. To dialogue with the data, we used content analysis as referential Bardin (2000), we work with a description of the material. The choice of this research technique is justified to believe that the text is a form of expression of the subject. In this context, after the break up of the texts of the interviews, we categorize the words and / or phrases that repeat, inferring, clusters them, working the meanings that constitute communication, and subsequently performing the grouping into categories. Undertake this research got us thinking about the importance of this work. Although maroon community has been disseminated through documentaries and scholarly works, has not yet been researched analysis as having bodily practices in physical education classes. We believe that this also constitutes itself as a way of strengthening the maroon culture, identifying cultural issues, and allowing the Maroons to rethink the role of schools as locus of continuity and discontinuity of culture.